2005
DOI: 10.1097/00004694-200501000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Coxa Magna and Final Outcome in Legg-Calve-Perthes Disease

Abstract: This study evaluated the final outcome of coxa magna that developed as a sequela of Legg-Calve-Perthes disease. The final outcomes at skeletal maturity were assessed by the Stulberg classification in 85 children with unilateral Perthes disease. Among them, 21 children had a bilateral arthrogram at the active stage of the disease, and the arthrogram measurements were compared with those measured at disease healing and at skeletal maturity. Coxa magna was observed in 53% (45/85), with a mean increase in 20.0 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Our study showed 72 hips (51% of the affected group) with radii of the contour of the articular sphere in the frontal plane larger than 2.65 cm, and this correlates with the previous report of "coxa magna" being present in a group of 85 hips after LCPD in 53%, when measuring the widest diameter of the femoral head on AP radiograms at skeletal maturity and considering the 10% difference between affected and unaffected sides as a threshold value (Rowe et al 2005).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study showed 72 hips (51% of the affected group) with radii of the contour of the articular sphere in the frontal plane larger than 2.65 cm, and this correlates with the previous report of "coxa magna" being present in a group of 85 hips after LCPD in 53%, when measuring the widest diameter of the femoral head on AP radiograms at skeletal maturity and considering the 10% difference between affected and unaffected sides as a threshold value (Rowe et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, within the LCPD group, the Stulberg Class III/IV/V subgroup had higher prevalences of both THA and hip osteoarthritis compared to the Stulberg Class I/II subgroup (P ¼ 0.04 and P ¼ 0.03, respectively) (Froberg et al 2011). Rowe et al (2005) showed that larger heads resulted in skeletal maturity with worse Stulberg class and larger possibility of having osteoarthritis later in life. These results agree with our findings that larger articular surfaces express more unfavourable stress distribution when compared to normal sized ones (Table 2), and with previous results (Kocjancic et al 2014) showing statistically significant correlation between stress gradient index and radiological Stulberg score.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[1][2][3][4] The grading system of choice for determining the long-term clinical outcome is that of Stulberg et al,4 which is recorded at skeletal maturity. While the lateral pillar classification is strongly predictive of outcome 5,6 it does not necessarily predict the outcome after surgery since it is usually assigned when treatment begins.…”
mentioning
confidence: 99%